1983
DOI: 10.4319/lo.1983.28.1.0165
|View full text |Cite
|
Sign up to set email alerts
|

Chemical speciation of antimony in marine algae

Abstract: An atomic absorption‐hydride generation technique was devised with an air/hydrogen flame system for determination of the speciation of antimony(III) and antimony(V) in marine algae. Antimony(III) is determined selectively at pH 4, total antimony after low temperature ashing of the dry algae using electrically excited oxygen atoms. Detection limits are 0.05 ng ± 10%. For the three marine algae (Ulva sp., Enteromorpha sp., and Sargassum sp.) sampled in San Diego Bay (California) seawater, Sb(V) is dominant. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
1

Year Published

1984
1984
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 0 publications
0
5
1
1
Order By: Relevance
“…the arsenosugars described by Edmonds and Francesconi (198 1)) make up most of the soluble arsenic content ( Table 1). In contrast, the methylantimony compounds were found neither by us in marine phytoplankton (Table 1) nor by Kantin (1983) in macro-algae. Digestion of the phytoplankton samples with conc.…”
Section: Methylated Species Of Arsenic and Antimonycontrasting
confidence: 56%
See 1 more Smart Citation
“…the arsenosugars described by Edmonds and Francesconi (198 1)) make up most of the soluble arsenic content ( Table 1). In contrast, the methylantimony compounds were found neither by us in marine phytoplankton (Table 1) nor by Kantin (1983) in macro-algae. Digestion of the phytoplankton samples with conc.…”
Section: Methylated Species Of Arsenic and Antimonycontrasting
confidence: 56%
“…Andreae and Klumpp (1979) have shown the ability of marine phytoplankton to reduce arsenic(V) to arsenic(II1) ic laboratory cultures. The presence of antimony(II1) in marine macro-algae was shown by Kantin (1983), who found that up to 30% of the antimony in Sargassum sp. is in the trivalent form.…”
Section: Resultsmentioning
confidence: 96%
“…It is known that Sb(V) can be abiotically reduced to Sb(III) by Fe(II)-containing minerals (56)(57)(58). A marine macroalga, Sargassum sp., was the first reported organism able to reduce Sb(V) in seawater (59). In the treatment of leishmaniasis, several studies suggested that Sb(V), when used as a prodrug medicine, might be reduced in both the vertebrate host and the parasites (60)(61)(62)(63).…”
Section: Microbial Antimony Cyclementioning
confidence: 99%
“…Under anaerobic conditions, some microbes can reduce Sb(V) to Sb(III). Kantin (1983) first reported that the macroalgae Sargassum sp. can reduce Sb(V) to Sb(III) in seawater.…”
Section: Antimony Resistance and Mechanism Of Sb-oxidizing Bacteriamentioning
confidence: 99%